Black howler monkey (Alouatta pigra) activity, foraging and seed dispersal patterns in shaded cocoa plantations versus rainforest in southern Mexico. Issue 9 (25th March 2014) - Zárate, Diego A.; Andresen, Ellen; Estrada, Alejandro; Serio‐silva, Juan Carlos
<x xml:space="preserve">Abstract</x> Recent evidence has shown that primates worldwide use agroecosystems as temporary or permanent habitats. Detailed information on how these primates are using these systems is scant, and yet their role as seed dispersers is often implied. The main objective of this study was to compare the activity, foraging patterns and seed dispersal role of black howler monkeys (Alouatta pigra) inhabiting shaded cocoa plantations and rainforest in southern Chiapas, Mexico. We gathered data on three monkey groups living in shaded cocoa plantations and three groups living in rainforest, using focal sampling, and collecting fecal samples. General activity and foraging patterns were similar in both habitats, with the exception that monkeys in the cocoa habitat spent more time feeding on petioles. Monkeys in shaded cocoa plantations dispersed 51, 369 seeds (4% were seeds ≥3 mm width) of 16 plant species. Monkeys in the rainforest dispersed 6, 536 seeds (78% were seeds ≥3 mm width) of 13 plant species. Our data suggest that the difference between habitats in the proportion of large versus small seeds dispersed reflects differences in fruit species abundance and availability in cocoa versus forest. Mean seed dispersal distances were statistically similar in both habitats (cocoa = 149 m, forest = 86 m). We conclude that the studied cocoa plantations provide all elements necessary to constitute a long‐term permanent habitat for black howler monkeys. In turn, howler monkeys living in these plantations are able to maintain their functional role as seed dispersers for those native tree and liana species present within their areas of activities. Am. J. Primatol. 76:890–899, 2014. © 2014 Wiley Periodicals, Inc.